The sexual satisfaction of women after labour — part II - Stadnicka, Grażyna; Łepecka-Klusek, Celina; Pilewska-Kozak, Anna; Pawłowska-Muc, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction/Aim. The aim of this research to check the influence of some factors on sexual satisfaction of women after childbirth. Material and methods. Research has been carried out amongst 360 women in the period of 3–6 months after labour. The authorial questionnaire as well as the survey questionnaire (Sexual Quality of Life Questionnaire Female) have both been used in the research. The statistical analysis has been carried out with the help of the computer software IBM SPSS Statistics version 21. The Mann-Whitney U test has been used in the statistical analysis. Results. The ages of the participants of the survey ranged between 18 to 43 years. For more than half of the research participants 62.77% (n = 226) it was their first labour, while for the remaining women 37.23% (n = 134) their second or the following one. 67.22% (n = 242) of the women gave birth to their children through vaginal delivery, while 32.78% (n = 118) through a Caesarean section. Primiparas experienced a better quality of the sexual life when compared to multiparas (p = 0.001). The women who have experienced a vaginal delivery without the need for episiotomy have reported the highest satisfaction with their sexual lives (Me = 92.00). The observed statistically significant differences (p = 0.012) in the level of the sexual satisfaction between the groups of the research participants without the symptoms of and those suffering from the symptoms of stress urinary incontinence. Conclusions. The subjective evaluation of the satisfaction with the sexual intercourse amongst women in the post-partum period seems to be dependent on the number of births, the method of child delivery, and the occurrence of symptoms of stress urinary incontinence.